Influence of medium composition on the characteristics of a denitrifying biofilm formed by alcaligenes denitrificans in a fluidised bed reactor - Alves, C. F. (2002)
The influence of the ratio carbon/nitrogen and phosphorus concentration on the performance of a biofilm fluidised bed reactor used for denitrification and on the properties of the biofilm was studied. Although the removal efficiencies of C and N reached steady-state values, the thickness of the biofilm steadily increased. The dry density of the biofilm did not seem to be dependent on the loading conditions, although a denser biofilm was obtained when there was no nutrient limitation that corresponded to the complete removal of nitrate and carbon. The composition of the biofilm in terms of proteins and polysaccharides changed with the C/N ratio and P concentrations. Higher denitrifying activities, which were obtained with increasing P concentrations, were related with higher protein content, since metabolism was shifted from polysaccharide production towards cell production. The thickness and the density of the biofilms were related mainly with the shear stress in the reactor and the composition of biofilms was dependent on the composition of the medium and related with higher activities of the microorganisms.